Homicide followed by suicide in Porto Alegre city, Brazil - SÁ, Samantha Dubugras (2007)
This paper intended to characterize the profile of individuals who have committed homicide followed by suicide in Porto Alegre, during an 8-year period. The information about the events were gotten by newspaper articles and police inquiries researches, and through informants’ interviews. In the 14 cases located, the event seems to be a gender-related phenomenon, as men were the killers, while women and childrenwere the victims. The most used method for both the homicide and suicide was gunshot. The victim’s home was the place where most homicides and suicides were committed, usually during the morning. In five cases, the event triggers were jealousy, threats or end of arelationship. The aggressor had problems in his primary support group, signs of impulsiveness , aggressiveness, alcohol abuse and criminal records, especially due to violence against his own family.